La comunicación asertiva y su influencia en la satisfacción de los usuarios del área de quirófano del centro clínico quirúrgico ambulatorio Hospital del Día área de quirófano norte Tarqui en la ciudad de Guayaquil, año 2017 - Ríos Liberio, Ana Estefanía (2017)
Patients who go to the operating room of the Outpatient Surgical Clinical Center of the North-Tarqui Hospital in the city of Guayaquil usually do so, suffering from an illness that requires special care. Therefore, it is even more important to deal with an assertive communication where the kindness and the appropriate and timely response prevail. However, this is not always the case. In the work experience of the authors, insufficiencies have been found in the assertive communication that affects the satisfaction of the users……